Unmasking theatre design a designer's guide to finding inspiration and cultivating creativity - Porter, Lynne 1960- (New York Focal Press, 2015)
"Every great design has its beginnings in a great idea, whether your medium of choice is scenery, costume, lighting, sound, or projections. Unmasking Theatre Design shows you how to cultivate creative thinking skills through every step of theatre design - from the first play reading to the finished design presentation. This book reveals how creative designers think in order to create unique and appropriate works for individual productions, and will teach you how to comprehend the nature of the design task at hand, gather inspiration, generate potential ideas for a new design, and develop a finished look through renderings and models. The exercises presented in this book demystify the design process by providing you with specific actions that will help you get on track toward fully-formed designs. Revealing the inner workings of the design process, both theoretically and practically, Unmasking Theatre Design will jumpstart the creative processes of designers at all levels, from student to professionals, as you construct new production designs"--Provided by publisher.
Includes bibliographical references (pages 273-275) and index.
Keywords: Theater -- Production and direction -- Handbooks, manuals, etc; Drama -- Technique -- Handbooks, manuals, etc